International personal selling and real estate : complications and opportunities - Baack, Daniel W., (SAGE knowledge. Cases., 2016)
This case study investigates the different factors that must be considered by individuals and businesses wishing to market real estate and property on an international basis. For example, methods of communication, government restrictions or cultural differences in the terms of property ownership may present unique challenges.